1988
DOI: 10.1056/nejm198809013190904
|View full text |Cite
|
Sign up to set email alerts
|

Nerve Glucose, Fructose, Sorbitol,myo-Inositol, and Fiber Degeneration and Regeneration in Diabetic Neuropathy

Abstract: We measured the alcohol sugars in sural nerves from 11 controls, 21 conventionally treated patients with diabetes and neuropathy, and 4 diabetics without neuropathy. The results were related to metabolic control and to clinical, neuropathological, and morphometric abnormalities in the nerves. The mean endoneurial glucose, fructose, and sorbitol values were higher in diabetic patients than in controls. Linear regression analysis revealed that nerve sorbitol content in the diabetics was inversely related to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
92
2
3

Year Published

1995
1995
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 242 publications
(102 citation statements)
references
References 46 publications
5
92
2
3
Order By: Relevance
“…Therefore quantification of the early pathological changes will allow the identification of vulnerable cell types and fibre populations involved in the genesis of human diabetic neuropathy. The present study confirms the excess of paranodal and segmental demyelination with remyelination without significant axonal degeneration observed previously in patients with minimal neuropathy [9,33]. However, we did not show a reduction in either myelinated fibre or axonal area, nor did we show evidence of axonal atrophy.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Therefore quantification of the early pathological changes will allow the identification of vulnerable cell types and fibre populations involved in the genesis of human diabetic neuropathy. The present study confirms the excess of paranodal and segmental demyelination with remyelination without significant axonal degeneration observed previously in patients with minimal neuropathy [9,33]. However, we did not show a reduction in either myelinated fibre or axonal area, nor did we show evidence of axonal atrophy.…”
Section: Discussionsupporting
confidence: 92%
“…Alterations in nerve conduction velocity and amplitude have been considered to reflect underlying structural pathology of the myelinated fibres [30]. Such pathology includes demyelination and a significant loss of myelinated fibres due to axonal degeneration [9,10]. In addition axonal atrophy and axo-glial dysjunction have also been demonstrated in some [31,32] but not in other [20,21,33] studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With the rationale that excessive flux of glucose via this enzyme contributes to diabetic injury, several AKR1B-specific inhibitors have been synthesized. Initial small-scale clinical trials showed that inhibition of this enzyme could ameliorate symptomatic somatic and autonomic neuropathies (Jaspan et al, 1983), improve joint mobility (Eaton et al, 1985) and could prevent or delay fiber degeneration in neuropathy (Dyck et al, 1988) and partially correct nerve conduction defects in diabetics (Sima et al, 1988). Later, large-scale clinical trials, however, failed to demonstrate clear benefit and were marred with non-specific sensitivity reactions or off-target effects.…”
Section: Iii) Inhibitorsmentioning
confidence: 99%
“…Other symptoms includes an inability to detect heat and cold, cutaneous hyperaesthesia, loss of vibration sensation and paradoxically, the loss of pain perception. The pathophysiology of the condition remains unclear, although it has been associated with peripheral demyelination, a decrease in peripheral nerve conduction and degeneration of myelinated and unmyelinated sensory fibers [11] . Hyperglycemia can induce oxidative stress via glucose autooxidation and the subsequent formation of advanced glycation end products, disruption of the polyol pathway, altered eicosanoid metabolism and decreased antioxidant defenses [14,8] .…”
Section: Introductionmentioning
confidence: 99%